Halal Food Supply Chain Management, For Small And Medium Enterprises Food & Beverages - Berampu, Lailan Tawila; Taufiqurrahman, Taufiqurrahman; Latif, Muhammad; Efni, Yulia (Journal La Sociale, 2026)
This study aims to analyze the influence of Halal Food Supply Chain Management (HFSCM) on the competitive advantage of Food & Beverages MSMEs fostered by Pekanbaru SOE Houses. The background of the research is based on the low level of halal certification and the lack of optimal implementation of halal supply chains in the culinary MSME sector, even though Indonesia has great potential in the halal industry. The study used a quantitative approach with the SEM-PLS method and involved 130 active MSME respondents. HFSCM is measured through six dimensions: halal raw material, halal process, halal packaging, halal warehousing, halal transportation, and halal distribution. Competitive advantage is measured through product quality, innovation, delivery accuracy, service, and differentiation. The results of the study show that the entire hypothesis is accepted. HFSCM has been proven to have a positive and significant influence on the competitive advantage of MSMEs. Supplier Partnership is the most dominant factor in increasing competitiveness, while Human Development is the strongest predictor of HFSCM. The R² value of 74.3% in the competitive advantage variable and 69.2% in HFSCM indicates the high predictive power of the model. This study confirms that the implementation of a halal supply chain as a whole increases consumer confidence, operational quality, and the competitive position of MSMEs. These findings make a practical contribution to the development of MSMEs, especially in strengthening human resource competencies, supplier partnerships, and digital literacy to support the sustainable implementation of HFSCM.